(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background : Acute appendicitis is one of the commonest surgical emergencies in children and malnutrition is prevalent in the country. This study was designed to compare if complicated appendicitis occurs more in malnourished children. Materials and methods: This cross-sectional study was conducted in Department of Paediatric Surgery, Chittagong Medical College Hospital from March 2017 to December 2019 with 155 children. Anthropometric measurements (Height, weight, Mid Upper Arm Circumference (MUAC) Triceps Skin Fold Thickness (TSFT) were recorded and biochemical assessment (Haemoglobin, albumin and total lymphocyte count) were done before surgery. Patients were grouped into two groups: Group A (Acute uncomplicated appendicitis; n=65) and Group B (Acute complicated appendicitis, n=90). Anthropometric and biochemical indices were compared between these two groups. Results: Age ranged from 2 -12 years (Mean 9.2 ±2.5 years) (Male: female- 1.35:1). Among the five anthropometric indices abnormal measurements in Group A vs Group B were respectively. Abnormal TSFT (73.8% vs 80%, p=0.4) wasting (38.5% vs 44.4%, p=0.4) low MUAC for age (13.8% vs 17.8%, p=0.8) low weight for age (30.8% vs 36.7%, p=0.5) and low height for age (21.5% vs 24.4%, p=0.7) low albumin (52.3% vs 83.3%, p<0,001); low haemoglobin (61.5% vs 60.0%, p=0.6)) and low total lymphocyte count (39.5% vs 44.8%, p=0.7). Conclusions: Malnutrition was widely prevalent in both groups. Although the proportion of malnutrition was more with acute complicated appendicitis, it was not statistically significant. The lower serum albumin level in these patients might be due to the consequence of the disease rather than prevailing malnutrition. JCMCTA 2022 ; 33 (1) : 66-70